2012
DOI: 10.1093/alcalc/ags014
|View full text |Cite
|
Sign up to set email alerts
|

Performance on an Everyday Life Activity in Persons Diagnosed with Alcohol Dependency Compared to Healthy Controls: Relations between a Computerized Shopping Task and Cognitive and Clinical Variables†

Abstract: This computerized task is a good proxy measure of the level of everyday life and cognitive functioning of persons diagnosed with alcohol dependency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Nevertheless, two studies that administered the same computerized shopping task, albeit with patients with schizophrenia (Larøi et al, 2010) and alcohol dependency (Laloyaux et al, 2012), also observed similar results. Interestingly, in all three studies (including the present study), the variable Total time to complete the shopping task significantly differentiated between clinical and healthy control groups and correlated significantly with a number of cognitive and clinical variables, including level of real world functioning, suggesting that this variable is the most sensitive to real world and cognitive impairments.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Nevertheless, two studies that administered the same computerized shopping task, albeit with patients with schizophrenia (Larøi et al, 2010) and alcohol dependency (Laloyaux et al, 2012), also observed similar results. Interestingly, in all three studies (including the present study), the variable Total time to complete the shopping task significantly differentiated between clinical and healthy control groups and correlated significantly with a number of cognitive and clinical variables, including level of real world functioning, suggesting that this variable is the most sensitive to real world and cognitive impairments.…”
Section: Discussionmentioning
confidence: 58%
“…Moreover, several studies using the same shopping task with persons diagnosed with schizophrenia and alcoholic dependency (Larøi et al, 2010;Laloyaux et al, 2012) have already demonstrated good sensitivity in that performance on the task significantly differentiated between clinical groups and healthy controls. Moreover, performance on the shopping task in these studies was significantly related to real world functioning measures (convergent validity).…”
Section: Computerized Shopping Taskmentioning
confidence: 99%
“…Studies with other disorders have shown the importance of duration of illness/clinical staging in their presentation. In the case of substance use disorders, studies have suggested that longer duration of illness is correlated with more cognitive deficits (e.g., response inhibition and cognitive flexibility Laloyaux et al, 2012;Monterosso et al, 2005). Studies have further found that longer duration of illness may be associated with structural abnormalities such as gray and white matter volumes reductions, as well as decreased brain activation, in substance use disorders (Bjork et al, 2003;Ersche et al, 2011;Sjoerds et al, 2014, bipolar disorder (in the area of the hippocampus and amygdala; Gildengers et al, 2014), body dysmorphic disorder (right orbitofrontal cortex volumes; Buchanan et al, 2014), and obsessive-compulsive disorder (hippocampus and amygdala; Atmaca et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of alcohol and other substance use disorders, studies have suggested that longer duration of alcohol use disorder (AUD), methamphetamine use disorder, and heroin use are correlated with more cognitive deficits. This is particularly true for response inhibition, reaction time, and cognitive flexibility (Laloyaux et al., 2012; Martinovic-Mitrovic et al., 2008; Monterosso, Aron, Cordova, Xu, & London, 2005). Moreover, research in AUD suggested that early onset of problems with alcohol is associated with stronger genetic susceptibility and poorer treatment outcome (Babor et al., 1992; Carpenter & Hasin, 2001; Cloninger, 1987; Schuckit et al., 1995).…”
Section: Introductionmentioning
confidence: 99%